METHODOLOGICAL PRECONDITIONS OF FUTURE TEACHER PREPARATION FOR VIRTUAL MULTISUBJECT INTERACTION IN THE EDUCATIONAL PROCESS - Spivakovska, Є.О. (Journal of Information Technologies in Education (ITE), 2016)
The essence of methodological approaches defined as the foundation for the development of pedagogical system aimed at preparation of future teachers for the professional activity in virtual multisubject learning environment has been substantiated in the article. The following are the approaches: system-subjective, synergetic, reflexive, competence-based, resource-based,subject-oriented, and dialogue-based. Each of the mentioned approaches singled out certain methodological principles following which brings about effective realization of the developed pedagogical system. Much attention has been paid to specific methodological principles which determine the core sense of the preparation of future teachers for the virtual multisubject interaction in the educational process: the principle of the subject’s self-realization, selfdevelopment and self-improvement encouragement, the principle of differential and individual approach which provides the development of qualities of subjectivity within every subject of educational interaction, the principle of integration (which predetermines the engagement of all possible resources, both internal and external, for the complex solution of educational tasks completed by the subjects participating in the multisubject educational environment in the process of dialogue-based (multisubject) interaction), and the principle of exploitation of potential capabilities of the subject of interaction. The substantiated methodological basis has made it possible to model the system of preparation of a future teacher of Humanities for the professional activity in virtual multisubject learning environment.